Impact of Intermittent Fasting Combined With High-Intensity Interval Training on Body Composition, Metabolic Biomarkers, and Physical Fitness in Women With Obesity - Batitucci, Gabriela; Faria Junior, Eli V.; Nogueira, Jonatas E.; Brandão, Camila F. C.; Abud, Gabriela F.; Ortiz, Gabriela U.; Marchini, Julio S.; Freitas, Ellen C. (Frontiers in Nutrition, 2022)
Background: Intermittent fasting (IF) is a dietary approach that is widely popular due to its effects on weight loss and body fat, but it does not appear to ensure muscle mass preservation. Incorporating high-intensity interval training (HIIT) into an individual's routine could be an attractive and viable therapeutic option for improving body composition, lifestyle and health promotion. Problematizing the emerging situation of fighting obesity, led us to clarify gaps about IF and hypothesize that IF and HIIT in conjunction may protect against muscle mass decline without impairing nitrogen balance (NB), in addition to improving the physical fitness of women with obesity. Objectives: To evaluate the effects of IF alone and combined with HIIT on body composition, NB and strength and physical fitness in women with obesity. Methods: Thirty-six women (BMI 34.0 ± 3.2; 32.2 ± 4.4 years) participated and were randomly distributed into 3 groups: 1. Intermittent fasting combined with exercise group (IF+EX); 2. Exercise group (EX); and 3. Intermittent fasting group (IF). The interventions took place over 8 weeks and all evaluations were performed before and after the intervention period. The HIIT circuit was performed 3x/week, for 25 minutes/session, at 70-85% of the maximum heart rate. 5:2 intermittent calorie restriction protocol was performed 2x/week, 18h fasting:6h restricted feeding. Resting metabolic rate (RMR) was measured by indirect calorimetry, body composition by BodPod®, NB from urinary nitrogen, food consumption by food records and physical and strength performance were measured by physical tests. ANOVA two-way repeated measures mixed model was performed followed by Sidak post hoc (p < 0.05). This project was registered in ClinicalTrials.gov, NCT05237154. Results: There were a reduction in body weight (P = 0.012) and BMI (P = 0.031) in the IF+EX group. There was body fat loss in the IF+EX group (-4%) and in the EX group (-2.3%), an increase in fat-free mass in the IF+EX group (+3.3%) and also in the EX group (+2%) and NB equilibrium in all groups. All parameters of aerobic capacity and strength improved. Conclusions: Combining IF with HIIT can promote increments in fat-free mass, NB equilibrium and improve physical fitness and strength.